2018
DOI: 10.3389/fpls.2018.00860
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Variation of Pumpkin (Cucurbita maxima cv. Big Max) Nectar and Nectaries as Determined by Proteomics and Metabolomics

Abstract: Nectar is a floral reward that sustains mutualisms with pollinators, which in turn, improves fruit set. While it is known that nectar is a chemically complex solution, extensive identification and quantification of this complexity has been lacking. Cucurbita maxima cv. Big Max, like many cucurbits, is monoecious with separate male and female flowers. Attraction of bees to the flowers through the reward of nectar is essential for reproductive success in this economically valuable crop. In this study, the sex-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…As previously noted, nectars are much more complex than simple sugar–water, containing many classes of biologically relevant solutes that influence not only pollinator visitation, but also impact microbial growth (Nicolson & Thornburg, ; Roy et al., ). In this study, we reliably identified over 40 metabolites in both male and female nectar, which is similar to an analysis of C. maxima (pumpkin) nectar (Chatt et al., ). While male nectar preferentially accumulates certain metabolites as compared to female nectar (Figure ), the causes or consequences of these differences are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously noted, nectars are much more complex than simple sugar–water, containing many classes of biologically relevant solutes that influence not only pollinator visitation, but also impact microbial growth (Nicolson & Thornburg, ; Roy et al., ). In this study, we reliably identified over 40 metabolites in both male and female nectar, which is similar to an analysis of C. maxima (pumpkin) nectar (Chatt et al., ). While male nectar preferentially accumulates certain metabolites as compared to female nectar (Figure ), the causes or consequences of these differences are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…However, a majority of studies, particularly in Arabidopsis, have largely been dependent on genetic strategies, and biochemical confirmation of the conclusions have been hampered by the small size of Arabidopsis flowers and small amounts of nectar produced by these flowers. In contrast, plants in the Cucurbita genus, such as C. pepo , develop much larger flowers and produce >100‐fold more nectar per flower than Arabidopsis, and thus are more amenable to biochemical studies on nectar production [e.g., (Chatt et al., ; Nepi, Pacini, & Willemse, ; Nepi et al., , )].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, SKU5 is up-regulated in mature cucumber pollen grains; it was proposed that SKU5 may function during cucumber floral development and pollen formation (Pawełkowicz et al, 2019) and is generally associated with two-directional growth and the regulation of cell wall expansion (Sedbrook et al, 2002). M-linked polymorphisms were found within an aldolase-coding gene; a proteomic study of pumpkin nectar found an aldolase uniquely in male nectar (Chatt et al, 2018), and a putative aldolase- (Devani et al, 2019). Based on these functions, the genes in this region appear to enhance maleness, and existing literature has not associated these genes explicitly with pistil fertility to the authors knowledge.…”
Section: Sex-linked Genes Have Distinct Expression Patterns and Are Hmentioning
confidence: 99%
“…These studies provide evidence to support an eccrine-based model of nectar synthesis and secretion, which utilizes pores and transporters for movement of pre-nectar metabolites through the plasma membrane of nectariferous parenchyma tissues [reviewed by (Roy et al, 2017)]. In this model, prior to nectar secretion the ‘pre-nectar’ sugar metabolites are delivered through the vasculature and stored in the nectary parenchyma, primarily as starch (Chatt et al, 2018; Lin et al, 2014; Peng et al, 2004; Ren et al, 2007; Solhaug et al, 2019). At the time of nectar secretion, the stored starch is rapidly degraded, and the products are used to synthesize sucrose through the enzymatic action of sucrose-phosphate synthases (SPS) and sucrose-phosphate phosphatases.…”
Section: Introductionmentioning
confidence: 97%
“…The sucrose is exported into the apoplasm in a concentration dependent manner via the uniporter SWEET9, and subsequently hydrolyzed by cell wall invertase (CWINV4), to the hexose components glucose and fructose, thereby maintaining the sucrose concentration gradient (Lin et al, 2014; Ruhlmann et al, 2010). The last step of sucrose hydrolysis is critical to the production of hexose-rich nectars (Ruhlmann et al, 2010), but may play a minimal role in production of sucrose-rich nectars (Chatt et al, 2018; Solhaug et al, 2019).…”
Section: Introductionmentioning
confidence: 99%